Dynamical analysis of physiologic signals - Noraznita Ramli. (2010)
The report provides a review study in the patterns and dynamics of physiological time series such as the human heart rate. The human heart rate consists of “real world” physiological signals derived from human subjects. They are available online and called Fantasia Database. [3, 4]